A GABAergic and peptidergic sleep neuron as a locomotion stop neuron with compartmentalized Ca2+ dynamics - Wagner Steuer Costa (Nature Portfolio, 2019)
The GABAergic and peptidergic neuron RIS mediates sleep in Caenorhabditis elegans. The authors demonstrated here that RIS also functions as a locomotion stop neuron. Its optogenetic stimulation caused acute and persistent inhibition of locomotion, and brief intrinsic RIS activity preceded slowing.